The diversity and applications of microbial iron metabolism and iron-containing proteins - Haichun Gao; Ingrid Span (Communications Biology)
This collection reflects research that will advance the understanding of hemoproteins, iron-sulfur cluster proteins and other iron-containing proteins, proteins involved in homeostasis of iron/heme and their regulation, or ecological impacts of iron/heme on interacting hosts and microbial communities.